Determinação de compostos bioativos da polpa de bacaba liofilizada - VIANA, Arliane Amaral (2023)
Noncommunicable chronic diseases (NCDs) are the leading cause of disease and death worldwide and are correlated with oxidative stress. Therefore, we seek to identify antioxidant food sources in order to prevent NCDs. The bacaba with excellent nutritional value and rich in lipid bioactive compounds stands out. Thus, the objective of this research was to determine the bioactive compounds of lyophilized bacaba pulp in order to add value to their functional capacity. The pulp was obtained from the Ver-o-Peso market in Belém, State of Pará, and then the material was lyophilized and characterized by physical and chemical aspects (water activity, hydrogen potential, total titratable acidity, total soluble solids), and in bioactive compounds such as total phenolics, anthocyanins, flavonoids, total carotenoids and natural pigments (chlorophyll a, chlorophyll b, lycopene). The study confirmed the functional capacity of lyophilized bacaba pulp by identifying an average of 181.11 (mg / 100g) total phenolic compounds, 21.32 (mg / 100g) anthocyanins, flavonoids 54.25 (mg / 100g), and carotenoids. 10.68 (mg / 100g). It was possible to observe high value of phenolic compounds and total carotenoids when compared with other fruits of the Amazon region. It is concluded that the results obtained were promising presenting high values of bioactive compounds adding functional, nutritional and commercial value to the lyophilized pulp of this fruit.